Conceptualizing and measuring positive youth development in sport: a scoping review - Bruner, M. W.; McLaren, C. D.; Sutcliffe, J. T.; Gardner, L. A.; Vella, S. A. (International Review of Sport and Exercise Psychology, 2022)
Despite the pervasive belief that sport can serve as a vital context for positive youth development (PYD), the associated empirical evidence to support these claims is less compelling. To advance the field, the purpose of this scoping review was to better understand how sport-based PYD researchers conceptualize PYD, and both operationally define and measure PYD outcomes. A final sample of 78 non-experimental, quantitative research articles involving 90,665 youth (Mage = 14.16 years) met inclusion criteria. Results revealed a wide and inconsistent array of (a) conceptual models and definitions for PYD, (b) constructs used to operationalize PYD, and (c) measures used to assess these PYD constructs. Only 38 of the studies (48%) explicitly conceptualized PYD using a formal definition and/or framework and there were a total of 243 unique operational definitions to represent PYD through sport (assessed a total of 632 times). In light of these findings, we offer a set of recommendations with the intent to strengthen future quantitative, sport-based PYD research. We believe that adherence to these guidelines carries the potential to enhance future theoretical and practical contributions, and help to better understand sport as a vehicle for positive development for youth.